Unveiling the effects of key factors in enhancing gastroesophageal reflux: A fluid-structure analysis before and after laparoscopic sleeve gastrectomy. (April 2023) - Toniolo, Ilaria; Berardo, Alice; Gagner, Michel; Foletto, Mirto; Carniel, Emanuele Luigi
Highlights: A reverse fluid flux from the stomach to the oesophagus was observed. Wider His-angle in the pre-surgical configuration, greater flux flow. Greater pressure with increasing His-angle proved the maximum flux flow. Larger antrum region after surgery, lower final flux for all the His-angles. Greater the bolus viscosity, lower the reflux flow. Abstract: Background and Objectives: Gastro-oesophageal reflux disease (GERD) consists in the passage of gastric acid content from the stomach to the oesophagus, causing burns and deteriorating the quality of life. Laparoscopic Sleeve Gastrectomy (LSG) could induce de novo GERD and worsen pre-existing GERD because of the higher gastric pressurisation, reduction of stomach volume and a wider His-angle. In the proposed work, various computational gastric 2D models were developed to understand the effects of variables such as the His-angle, the antral dimension, and the bolus viscosity on the reflux increase. Methods: Fluid-Structure Interaction (FSI) computational models which couple the solid mechanics of the gastric wall, and the fluid domain of the bolus, have been developed to shed light on biomechanical aspects of GERD after LSG. A closure was imposed to the lower oesophageal sphincter (LES) mimicking what happens physiologically after food intake. Results: Results showed that the configuration prone to higher reflux flow was the post-surgical 65° model with a staple line starting directly from the pylorus without antral preservation, for all considered viscosities. Increasing viscosity, reflux flow decreased. Post-surgical refluxes were higher than pre-ones and decreased with increasing antrum preservation. Conclusions: These results could be a starting point for analysis of anatomical features, bariatric surgery and GERD occurrence. Further studies based on 3D geometries need to be performed.